Smoking Patterns among Primary School Students in Turkey. (2006) - Uncu, Yesim; Irgil, Emel; Karadag, Mehmet
Abstract : Cigarette smoking continues to be a threat to global health. The number of cigarettes smoked per person tends to increase each year, and the age of starting seems to be dropping. The research related to cigarette smoking conducted among young people generally studied high school or university students. However, studies have shown that students usually start smoking during the primary school period out of curiosity or imitation. The purpose of the present study was to find the prevalence of cigarette smoking among primary school students and the reasons for starting smoking, and to determine the characteristics of cigarette smoking of their parents. This study was conducted among 17 primary schools chosen according to their socioeconomic situations in different municipality districts in Turkey, with 9, 408 students participating. Data were obtained by questionnaire. The mean age to start smoking was 11.7 ± 1.6; 82.9% of the students who took part in this study had never smoked before, 13.4% had tried smoking at least once, and 3.7% had been smoking regularly. The biggest reason for smoking was just curiosity or imitation. It was determined that a risk factor for students to start smoking was parents who smoke. The 17% smoking rate among primary school students was high in our opinion and prevention studies initiated. In addition, the effects of cigarette-smoking parents on students who start smoking should also be considered.